Developing event specific strength for the javelin throw - Young, M.
The javelin throw is very different from the other throwing events. As a result special consideration must be taken when developing a training program to produce event specific strength. Coaches must remember that an athletes` adaptation to training is specific to the stress placed on them. This article will focus on exercises and methods to help a javelin thrower increase this specific strength.